Rancang Bangun Sistem Kendali Otomatis pada Simulator Transfer Carriage Palm Oil Mill Berbasis Time Delay Relay - Ahmad Mahfud (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
Transfer carriage is a tool that serves to move the lorry from the rail track loading ramp to the sterilizer rail track. Utilization of push-botton on still done on the process of operation manually, so still need manpower. The purpose of this research is to know: 1) how to operate the carriage transfer simulator; 2) the circuit used for the transfer carirage automation system; 3) the time required for switching the truck miniature from transfer carriage to the sterilizer rail track; and 4) the advantage that can be obtained by the use of the transfer carriage relay. Data collection is done through observation of the object under study, interviews with parties related to the object under study and literature study. The development of automated control system device is preferred to be able to automatically drive a lorry from the charging point to the lane rail line in front of the sterilizer. The result show that: 1) the transfer carriage simulator is operated by utilizing relays as an automatic driver of the existing contacts, and supplied with an adapter-reduced voltage from 220 volts to 5 volts; 2) automated transfer carriage system supported by a reverse forward control circuit; 3) time of miniature transfer of lorries from transfer carriage to sterilizer rail track for 3 sec; and 4) the use of operational transfer carriage relay can reduce the hazard level in the manpower, which potentially occurs when activities are done manually.